Market adoption of reverse factoring. Issue 3 (7th April 2015) - Dello Iacono, Umberto; Reindorp, Matthew; Dellaert, Nico
Abstract : Purpose: – The purpose of this paper is to show that market dynamics can significantly influence the lifecycle and value of a supply chain finance (SCF) arrangement. Design/methodology/approach: – Based on a review of scientific and trade literature, the authors construct a model of market dynamics for reverse factoring, a specific type of SCF arrangement. The authors assume that firms' participation in a reverse factoring arrangement is determined by the direct benefits they can derive from it. The authors analyse the model by means of simulation in system dynamics. Findings: – The authors identify the following market factors as key for direct benefits: competition, interest rates, receivables volumes, and firms' working capital goals. The authors find that reverse factoring can yield direct benefits for all supply chain participants, but that these benefits are highly sensitive to market conditions. Research limitations/implications: – The model is stylized, but this study shows the need for further research on the dynamic aspects of SCF arrangements. Practical implications: – The authors show that supply chain actors should carefully consider the expected evolution of market factors when deciding on participation in a reverse factoring arrangement. Originality/value: – Existing research on SCF arrangements almost exclusively considers a static context, where market factors take fixed, known values. The authors provide the first study that links the direct benefits of SCF arrangements to dynamic, interacting market factors. The authors utilize system dynamics, a methodology well-suited to the analysis of such settings, to show that a comprehensive assessment of SCF arrangements cannot neglect the evolutionary perspective.